The Science, Technology and Society (CTS) approach: a possibility of student motivation (Research, Society and Development, 2020)
In this article, which aims to identify in the didatic sequences with a focus on CTS evidence of motivation for the students, it presented a survey of scientific research about the CTS approach (Science, Technology and Society) in the classroom. It is a State of Know ledge, as it comprised the scope of the theme from consultations of a research source, being the Periodicals of the Coordination and Improvement of Higher Education Personnel (CAPES) that present Qualis A1 to B2. It was established as a time frame the last five years (2014 to 2019). In this period of time, a total of 920 published papers were presented. From this issue, 05 focus edon reporting experiences with the CTS approach in the classroom environment. In the analyzed articles, we noticed that the authors present in the didactic sequences indications of motivating teaching strategies presented by Bzuneck (2010) and thus, it is evident that the CTS approach is configured as a possibility for the promotion of the students' motivation in the leaning process.